2017
DOI: 10.18034/ajtp.v4i1.415
|View full text |Cite
|
Sign up to set email alerts
|

Financial Diagnosis Using CAMEL Model: Public versus Private Banks in Bangladesh

Abstract: The purpose of this paper is to empirically analyze the financial statement of two selected banks (One bank from the public sector and another one from the private) in Bangladesh during 2010-14. This study highlights ranking of two banks for their performance on CAMEL (Capital Adequacy; Asset Quality; Management Quality; Earnings Ability; and Liquidity) ratios. During the year Empirical results suggest that 2010-2014 NCCBL has scored better position of all the ratios except EPS, liquid assets to total assets a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Thus, by taking into account the lack of analysis on the Asian economy, this study considered Bangladesh as a key laboratory to explore the effect of income diversification and asset diversification on bank profitability. The latest literature indicates that several scholars have sought to study the determinants of bank profitability in Bangladesh (Rahman et al, 2015;Sufian and Habibullah, 2009;Robin et al, 2018;Sufian and Kamarudin, 2012;Hossain and Ahamed, 2015;Noman et al, 2015;Majumder and Rahman, 2017;Majumder and Li, 2018;Akter, 2017). However, to the best of our understanding, this is a specific study that considers bank diversification as an independent variable and a significant profitability determinant for Bangladesh's banking sector.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, by taking into account the lack of analysis on the Asian economy, this study considered Bangladesh as a key laboratory to explore the effect of income diversification and asset diversification on bank profitability. The latest literature indicates that several scholars have sought to study the determinants of bank profitability in Bangladesh (Rahman et al, 2015;Sufian and Habibullah, 2009;Robin et al, 2018;Sufian and Kamarudin, 2012;Hossain and Ahamed, 2015;Noman et al, 2015;Majumder and Rahman, 2017;Majumder and Li, 2018;Akter, 2017). However, to the best of our understanding, this is a specific study that considers bank diversification as an independent variable and a significant profitability determinant for Bangladesh's banking sector.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these institutions are required to maintain a minimum capital adequacy ratio (CAR) of at least eight (8) percent, computed by dividing the total eligible capital of these institutions by their total risk-weighted assets (RWA). This study utilizes the CAR to assess the performance of the banks since it is used extensively in the literature (Al-Najjar & Assous, 2021;Ab-Rahim et al, 2018;Altan et al, 2014;Atker, 2017;Kumar et al, 2022;Mishra & Aspal, 2012;Rauf, 2016;Roman & Sargu, 2013;Venkatesh & Suresh, 2014). According to Lad and Ghorpade (2022), banks with high capital adequacy ratios can satisfy their obligations, while those with low ratios are likely to face bankruptcy.…”
Section: Methodsmentioning
confidence: 99%
“…This study evaluates the asset quality of commercial banks using the ratio of non-performing loans to total loans. Several studies have utilised this ratio (Altan et al, 2014;Atker, 2017;Roman & Sargu, 2013;Venkatesh & Suresh, 2014) and found it had a significant relationship with bank performance (Derviz & Podpiera, 2008;Muhmad & Hashim, 2015;Ngoboka & Gatauwa, 2020;Nair et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations